2014
DOI: 10.1108/s1876-056220140000010045
|View full text |Cite
|
Sign up to set email alerts
|

Use of Touch Devices by Toddlers or Preschoolers: Observations and Findings from a Single-Case Study

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…This highlights the importance of attending to individual differences in young children’s experiences (Christensen and James, 2008; Rideout, 2014), as well as differences in information activities dependent on the specific interest under discussion. Additionally, consistent with the work of Agarwal (2014), children’s activities often moved between technological and non-technological environments, an element of children’s information practices that may be elided by the proliferation of research that focuses on children’s use of specific types of information and media platforms, such as internet search engines or television shows, rather than research that takes a more holistic approach to understanding children’s experiences with information and media across platforms (Woodfall and Zezulkova, 2016). Based on these findings, libraries and other information institutions [2] should continue to provide access to materials about a wide range of topics in diverse formats.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This highlights the importance of attending to individual differences in young children’s experiences (Christensen and James, 2008; Rideout, 2014), as well as differences in information activities dependent on the specific interest under discussion. Additionally, consistent with the work of Agarwal (2014), children’s activities often moved between technological and non-technological environments, an element of children’s information practices that may be elided by the proliferation of research that focuses on children’s use of specific types of information and media platforms, such as internet search engines or television shows, rather than research that takes a more holistic approach to understanding children’s experiences with information and media across platforms (Woodfall and Zezulkova, 2016). Based on these findings, libraries and other information institutions [2] should continue to provide access to materials about a wide range of topics in diverse formats.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the children’s self-described information seeking activities are consistent with prior research that has found that young children engage with various forms of media and technology (Agarwal, 2014; Barriage, 2016; Foss et al , 2012; Given et al , 2016; Havigerová and Haviger, 2014; Lovato et al , 2019; Oranç and Ruggeri, 2021; Rideout and Robb, 2020; Schlebbe, 2022), print sources (Barriage, 2022; Cooper, 2002; McKechnie, 2006; Shenton, 2004) and other people, including family members and peers (Barriage, 2016, 2022; Barriage and Searles, 2015; Shenton and Dixon, 2003b; Stewart, 2016), in their pursuit of information. Participants in this study also talked about experiences as ways of finding out new information.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mobile communication can have both positive effects in improving subjective well‐being (see e.g. Agarwal, ; Chan, ) and negative impacts upon excessive use, with smartphone addiction potentially leading to ill health, including physical, psychological, and social issues or affecting work‐life balance (Dén‐Nagy, ; Ding & Li, ; Haug et al, ). We investigate the following research questions: RQ1.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, a recent publication concentrated on the information seeking behaviors of children is focused exclusively on children and youth already engaged in formal schooling (Chelton & Cool, ). On the other hand, as researchers have begun focusing more broadly on information behavior, theory building around young children's information behaviors has captured some attention (Agarwal, ; Byrnes & Bernacki, ; Spink & Heinstrom, ).…”
Section: Introductionmentioning
confidence: 99%